Environmental factors associated with atopic dermatitis in children in urban and rural South Africa - Dewar, Janine (Department of Public Health and Family Medicine, 2025)
Background: Environmental exposures related to modern urban living, and the absence of protective rural exposures, may contribute to the high prevalence of childhood atopic dermatitis (AD). Objectives: To identify environmental exposures associated with AD in children living in three residential areas of South Africa. Methods: A total of 3144 children aged 3 to 11 years participated in 1999 in a cross-sectional study involving a suburban area, peri-urban informal settlement, and several villages in a remote rural district in South Africa. Caregivers of children within a modified case control subset of 739 children, consisting of 253 cases and 486 controls, completed a researcher-led 57-point questionnaire on environmental exposures. Bivariate and multivariate logistic regression models were used to determine statistically significant associations between environmental exposures and AD. Results: A total of 387 children in the urban area, 59 in the peri-urban area and 293 in the rural district were included. Mean age of participants was 6.8 years, and 53.9% were female. Multivariate analysis found that current exposure to mould (aOR 2.79; 95% CI 1.58 – 5.00), pesticides (aOR 1.73; 95% CI 1.24 – 2.42), stress events (aOR 2.37; 95% CI 1.19 – 4.75) and home infestation with fleas (aOR 1.73; 95% CI 1.24 – 2.42) increased odds of AD in our study population, as did weaning after 4 months (aOR 1.83; 95% CI 1.31 – 2.56), compared to earlier weaning. Conclusion: Our findings underscore the need for targeted interventions addressing indoor environmental air quality, use of indoor pesticides, and the impact of psychological stressors on the development of AD.